World Health Organization Policy Facing the Spread of COVID-19 in Indonesia - Mardiansyah Mardiansyah (Universitas Ahmad Dahlan, 2021)
Introduction to the Problem: This article discusses WHO policy set out in WHO protocol with 4 scenarios to be recommended to countries, namely countries without a case, countries with 1 or more cases, countries with cluster cases, and cluster with greater local transmission. In this case, Indonesia has a policy which is formed based on the WHO advice.Purpose/Objective of the Study: To find out whether the policies implemented to manage COVID-19 spread in Indonesia have similarities with the protocol of the WHO.Design/Methodology/Approach: Data were collected from primary and secondary data sources in the form of literature legal research and statute approach.Findings: The results showed that the spread, rather than preventing the COVID-19 outbreak from entering a territtory. As a result, there had been some considerations regarding to the implementation of WHO protocols, especially when closing an area or restricting national access. However, WHO policy is not an obligation to be implemented by a country because the most crucial thing is that anticipating the spread, breaking the spread chain and finding a cure from this health condition for patients.Paper Type: Research Article